Effect of pineapple harvest time on production and activities of stem bromelain - Costa, Laerte; Carvalho, Vânia Déa de (Pesquisa Agropecuaria Brasileira, 2014)
Harvesting season of pineapple stems (Ananas comosus L. cv. Smooth Cayenne) as to obtain the highest yield and activities of bromelain was studied and results reported. The stems were collected in Piumhí, in the Alto São Francisco region, MG, Brazil, and immediately transported to the laboratory of the Food Science Department at ESAL, for analyses. Chemical analyses showed that the best time to obtain the highest concentration and activities of bromelain was at 60 days after fruit harvest. Residue 3 showed more active bromelain (2.21 UP and 2.83 UP/mg) than residue 2 (1.25 UP and 2.28 UP/mg).